4CPS-150 The role of clinical pharmacist in emergency department. Issue 1 (23rd March 2023) - López-Vinardell, L; Merino-Mendez, R; Ruiz, J; Juanes, A; Socias-Cañellas, C; Bitlloch, M; Puig-Campmany, M; Campins, L
Abstract : Background and Importance: Pharmacist role in the emergency department (ED) has expanded over the last decades. However, there is limited published literature related to the interventions carried out in these units. Aim and Objectives: To perform a descriptive analysis of pharmaceutical interventions (PI) in ED, their acceptance rate, the main prescribing errors (PE) detected and the main Anatomical Therapeutic Chemical (ATC) groups involved. Material and Methods: A retrospective multicentric study was performed in the ED of a secondary and a tertiary hospital that serve about 685.000 total inhabitants with an overall of 228.550 emergency attendances per year. PI and PE were documented from Monday to Friday over a 4-hour period between June-September 2022. Dosage and frequency adjustment, formulary and drug modification, medication initiation and discontinuation, and pharmacokinetic monitoring were the PI included. PE were divided into three groups: lack of efficacy, potential safety problem or necessary/unnecessary treatment. Results: Out of 857 interventions registered, 40.4% were related to dosage adjustment; 32.0% medication initiation; 16.0% medication discontinuation; 5.6% drug modification; 3.5% pharmacokinetic monitoring; 1.5% frequency adjustment and 1.1% formulary interchange. Regarding PI, 71.9% were accepted, 21.9% were rejected and 6.2% were not evaluated because patients were discharged or dead. As for PE, 37.8% were related to necessary/unnecessary treatment, 32.6% potential safety problem and 29.6% to a lack of efficacy. The PE detected were reconciliation discrepancies (39.7%), underdose (21.4%), overdose (19.0%), duplicities (4.9%), contraindications (3.3%), adverse drug events (1.5%) and interactions (0.9%). The main ATC Groups involved were blood and blood forming organs (B) (21.7%), anti-infective for systemic use (J) (21.7%), cardiovascular system (C) (20.9%) and nervous system (N) (18.1%). Conclusion and Relevance: Dosage adjustments and drug therapy initiation were the most common documented interventions. More than half of PI were accepted. The most frequent PE were related to necessary/unnecessary treatment. The majority observed PE were reconciliation discrepancies. The main ATC groups involved were B, J and C. The great number of interventions and the high rate of acceptance seems to show that ED pharmacist, as a member of a multidisciplinary patient care team, is able to decrease the number of medicine errors and to improve the quality and safety of medical care. References and/or Acknowledgements: Thank you all. Conflict of Interest: No conflict of interest